Respon Masyarakat Muslim Terhadap Keberadaan Umat Kristen di Cikawungading Cipatujah Tasikmalaya Tahun 1996-2019 - Abdul Baits (Historia Madania: Jurnal Ilmu Sejarah, 2019)
This study aims to explain how the Muslim community responded to the presence of Christians in Cipatujah, as it is known that Christians came to Cipatujah around 1936, namely Javanese people from Salatiga who were brought by the leadership of a Dutch missionary named Tuan A. Van Emmerik. The method used in this research is the historical method by carrying out the stages starting from data collection (heuristics), levers (criticism), interpretation (interpretation) and writing (historiography). Data collection techniques used in this research are text study, observation. and interviews. The results of this study show that there have been ups and downs of relations between Muslims and Christians in Cipatujah. This can be seen from several conflicts that have occurred from the riots in 1996 to the burning of churches and Christian settlements in 2001. Keywords: Response, Muslims, Christians, Cipatujah.